Assessing the Impact of Fractured Zones Imaged by ERT on Groundwater Model Prediction: A Case Study in a Chalk Aquifer in Voort (Belgium) - Van Riet, Bjarn; Six, Simon; Walraevens, Kristine; Vandenbohede, Alexander; Hermans, Thomas (Frontiers in Water, 2022)
Fractured and karst aquifers are important groundwater reservoirs and are widely used to provide drinking water to the population. Because of the presence of the fractures with varying geometry and properties providing preferential flow paths, fractured aquifers are highly heterogeneous and difficult to characterize and model. In this context, geophysical methods can provide relevant spatially distributed data about the presence of fractures, that can be further integrated in hydrological and groundwater models. In this contribution, we present a case study of a groundwater extraction site in a fractured chalk aquifer in Voort (Belgium), used for the production of drinking water. First, the presence of fractures in the vicinity of the extraction site and their orientation is imaged using electrical resistivity tomography. Based on the available data and the objectives of the study, it is chosen to model only the groundwater component and to simplify the unsaturated zone processes through an average recharge rate. Then, the detected fractures are included in the groundwater model to improve the calibration and the predictive capacity of the model. The results show that a set of parallel fractures crosses the modeled area, whose orientation is in accordance with the tectonic setting. Including these fractures in the model, a more satisfactory calibration was achieved, helping to better understand the hydrogeological behavior of the aquifer. Finally, the acquired knowledge is used to propose new management scenarios for the extraction site minimizing its impact.